2010
DOI: 10.1258/jtt.2010.090809
|View full text |Cite
|
Sign up to set email alerts
|

The use of text messaging to improve asthma control: a pilot study using the mobile phone short messaging service (SMS)

Abstract: We have evaluated the feasibility of using the mobile phone short message service (SMS) for symptom monitoring in patients with asthma. All consecutive patients admitted to hospital for asthma during an 11-month period were considered for enrollment (n = 497). Those meeting the inclusion criteria were randomized into a control (n = 60) and intervention group (n = 60). Patients in the intervention group received SMS messages according to a structured workflow, while patients in the control group had no SMS supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 6 publications
2
49
1
Order By: Relevance
“…Successful use of systems alerting patients of the importance of medication adherence and determining intake status via SMS has been reported in many countries, including Kenya 36,37 and Cameron. 38 In the case of Kenya, one study found that adherence to ART was significantly higher ( p = 0.006) and suppression of viral load was significantly increased ( p = 0.04) in the group with access to SMS use (61.5% and 57.1%, respectively) compared with values in those without access (49.8% and 48.3%, respectively). 11 In addition, counseling via cellular phone was found to increase the level of adherence from 87% to 94% and improve self-efficacy ( p < 0.05).…”
Section: Health Management Systems Using Cellular Phonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful use of systems alerting patients of the importance of medication adherence and determining intake status via SMS has been reported in many countries, including Kenya 36,37 and Cameron. 38 In the case of Kenya, one study found that adherence to ART was significantly higher ( p = 0.006) and suppression of viral load was significantly increased ( p = 0.04) in the group with access to SMS use (61.5% and 57.1%, respectively) compared with values in those without access (49.8% and 48.3%, respectively). 11 In addition, counseling via cellular phone was found to increase the level of adherence from 87% to 94% and improve self-efficacy ( p < 0.05).…”
Section: Health Management Systems Using Cellular Phonesmentioning
confidence: 99%
“…Of the nine articles that examined the use of CPBMI by asthma patients and healthcare providers, eight were original research articles [14][15][16][17][37][38][39][40] examining asthma management programs using SMS, and the last was a qualitative study. 41 Of the eight original articles (Table 2), six investigated the effectiveness of using CPBMI in terms of convenience and self-management, focusing primarily on the use of CPBMI for self-management rather than for the control of asthma and its related adverse effects.…”
Section: Asthmamentioning
confidence: 99%
“…Patient education can be delivered via a wide range of settings, including conventional health care settings such as primary care (Charlton et al 1990;Mancuso et al 2011Turner et al 1998, tertiary care (Cowie et al 1997;Petkova 2008), and community pharmacies (Araujo et al 2012;Saini et al 2006;Santos et al 2010). In addition, emerging modalities of patient education provision include Internetbased education (Murray et al 2005;Prabhakaran et al 2010;Rasmussen et al 2005;Runge et al 2006) and mobile phone technology such as the use of short messaging service (SMS) (Liu et al 2011;Morahan-Martin 2004) and smartphone applications (BinDhim, McGeechan, and Trevena 2014). The efficacy of such patient education interventions has been investigated by several studies, and most have concluded that these interventions resulted in an improvement in asthma self-management practices and possibly a reduction of asthma-related morbidity in both adults and children (Araujo et al 2012;Murray et al 2005;Petkova 2008;Prabhakaran et al 2010;Rasmussen et al 2005;Runge et al 2006;Saini et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, emerging modalities of patient education provision include Internetbased education (Murray et al 2005;Prabhakaran et al 2010;Rasmussen et al 2005;Runge et al 2006) and mobile phone technology such as the use of short messaging service (SMS) (Liu et al 2011;Morahan-Martin 2004) and smartphone applications (BinDhim, McGeechan, and Trevena 2014). The efficacy of such patient education interventions has been investigated by several studies, and most have concluded that these interventions resulted in an improvement in asthma self-management practices and possibly a reduction of asthma-related morbidity in both adults and children (Araujo et al 2012;Murray et al 2005;Petkova 2008;Prabhakaran et al 2010;Rasmussen et al 2005;Runge et al 2006;Saini et al 2006). However, there are no studies that compare different modes of patient education provision.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine has been explored in many chronic diseases [20][21][22][23][24][25][26] and has recently gained much governmental attention. 27,28 However, its use in cancer patients is limited, particularly in Asia.…”
Section: Introductionmentioning
confidence: 99%